Trekksoft : sell direct everywhere - Frick, Melanie, (SAGE Knowledge. Cases., 2017)
A shared passion for outdoor adventures drove three young men in Switzerland to found TrekkSoft in 2010 - a company that offers an integrated software solution for online bookings in the tour and adventure segment - with the ambition to become a dominant player worldwide. Despite serving customers from all over the world, TrekkSoft had only established one subsidiary in the U.S. in the four years after its inception. In October 2014, the second financing round was approaching. The founders knew that further geographical expansion was crucial to satisfy the investors' high growth expectations, but internally they disagreed on which market to target: Mexico or Australia? Although they always had a one-market-after-another approach, investors were pushing for faster expansion, which led to another question: Should they go in the direction of both markets?The case shows students how important the market selection process for internationalising startups is and at the same time how company growth is influenced by the speed of the internationalising process. From an entrepreneurial perspective the case demonstrates the need of finding the right balance between investors' demands as well as founders' expectations. In addition, the case allows students to understand the relevance of personal and professional networks.